High-flame-retardant PVC composite material for charging pile drag chain

By using modified composite flame retardant in the drag chain material of the charging pile and using the modification technology of mica powder and silane coupling agent, the problem of insufficient flame retardancy of existing materials is solved, and high flame retardancy and wear resistance are achieved The effect of sexual performance significantly reduces safety risks.

CN119431970AInactive Publication Date: 2025-02-14GUANGDONG MINGBAO NEW MATERIAL TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411652141.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The flame retardancy of the existing charging pile drag chain materials is insufficient and easy to burn in power fires. The carbonized particles in the mica compound system are prone to fall off, resulting in protection failure, which poses a major safety hazard.

Method used

Using a composite flame retardant, the composite flame retardant is made of mica powder as the core material, and is surface treated with silane coupling agent KH-580, and is modified with active thiol and phosphate trichloride to form a ring-containing structure. The phosphate compound is induced by ultraviolet light to react with the thiol-knob on the surface of the coupling matrix to form a modified flame retardant, improving the flame retardant and wear resistance of the composite material.

Benefits of technology

It significantly improves the flame retardancy of the charging pile drag chain material, reaches the UL94 V-0 level, and shows excellent performance in the stability and protection effect of the ablation layer, reducing safety hazards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to a high-flame-retardant PVC composite material for a charging pile drag chain, and belongs to the technical field of polymer composite materials. The composite material is prepared from the following components: 10 to 15 weight percent of ABS (Acrylonitrile Butadiene Styrene) resin, 15 to 22 weight percent of composite flame retardant, 12 to 16 weight percent of plasticizer, 1.9 to 2.4 weight percent of stabilizer, 0.25 to 0.3 weight percent of antioxidant, 2.2 to 2.6 weight percent of lubricant and the balance of PVC (Polyvinyl Chloride) resin, according to the composite flame retardant, mica powder serves as a core material, a large number of compounds containing cyclic phosphate ester are introduced to the surface, a mica powder-carbide lamellar layer is formed in the ablation process, deep combustion is hindered, a carbonization layer on the surface of the core material plays a good transition role between an unablated PVC base body and the mica core material, the mica powder is prevented from falling off, and the service life of the flame retardant is prolonged. And the structure of the ablation layer is kept stable, and a good protection effect can still be kept after ablation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of polymer composite materials, and in particular, relates to a highly flame-retardant PVC composite material for a charging pile drag chain. Background Art

[0002] Charging pile, also known as electric vehicle charging station or electric vehicle power supply equipment, is a device that provides electric energy to electric vehicles, enabling them to store enough electricity to support their operation. As one of the key components of charging piles, charging pile drag chain is mainly used for the power connection part, which enables the cable between the charging pile body and the vehicle to be flexibly connected and rotated. Its reliability and stability directly affect the normal use of the charging pile and user experience.

[0003] PVC (polyvinyl chloride) is a polymer formed by the polymerization of vinyl chloride monomers in the presence of initiators such as peroxides and azo compounds or under the action of light or heat according to the free radical polymerization mechanism. It has good mechanical properties, certain wear resistance and insulation, and is widely available and inexpensive, making it a preferred material for charging pile drag chains. However, PVC, like other polymer materials, is not flame retardant enough, and it is difficult to rescue once an electrical fire occurs. In the prior art, a certain amount of flame retardant material is compounded into the PVC material to improve the flame retardancy. In drag chain materials, mica and organic phosphorus flame retardants are often compounded. The system can effectively improve the flame retardancy to a certain extent. However, in long-term research, it was found that under this system, the organophosphorus flame retardant is free in the composite material, and fine carbonized particles are formed during the ignition process. These carbonized particles are brittle and have low strength. They are easy to fall off during continuous ignition, which causes the combustion to penetrate deeper into the gaps of the mica powder, exposing the mica powder to form a loose ablation layer, which is easy to fall off under external influences and cause protection failure. Especially in charging pile drag chains, local breakdown and ablation often occur due to wear, mechanical loss, etc., and this type of ablation is not easy to detect, posing a great safety hazard. Summary of the invention

[0004] In order to solve the technical problems mentioned in the background technology, the object of the present invention is to provide a highly flame-retardant PVC composite material for a charging pile drag chain.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A highly flame-retardant PVC composite material for a charging pile drag chain, comprising the following components: ABS resin 10-15wt%, composite flame retardant 15-22wt%, plasticizer 12-16wt%, stabilizer 1.9-2.4wt%, antioxidant 0.25-0.3wt% and lubricant 2.2-2.6wt%, and the balance is PVC resin. The raw materials are melted, extruded and granulated to obtain a composite material.

[0006] The composite flame retardant is prepared by the following method: Step A1: pentaerythritol, anhydrous zinc chloride and anhydrous dioxane are mixed and added, dry nitrogen is introduced to replace the air in the reaction system, stirring is applied at 120-150 rpm, phosphorus oxychloride is slowly added, and after the addition, the temperature is raised to reflux and the reflux steam is absorbed by an alkali drying tube. The reflux time is controlled to be 6-8 hours. After the reaction is completed, dioxane is removed to obtain a flame retardant matrix; Step A2: the flame retardant substrate, triethylamine and acetonitrile are mixed, dry nitrogen is introduced to replace the air in the reaction system, the temperature is raised to 75-80° C., stirring is applied at 60-90 rpm, methylvinyldichlorosilane is slowly added to react for 12-15 hours, acetonitrile is removed after the reaction is completed, the substrate is washed with water and vacuum dried to obtain a modified flame retardant; Step A3: Mix the silane coupling agent KH-580 and the ethanol solution, adjust the pH value to 3-4 with formic acid and stir to hydrolyze for 1-1.3 hours, then add the mica powder and stir to disperse, let it stand for coupling for 24 hours, take the bottom precipitate and dry it to obtain a coupling matrix; Step A4: Mix the modified flame retardant, photoinitiator 1173 and dimethylacetamide, add the coupling matrix, mix and grind to make slurry, heat the slurry to 70-90°C and apply 150-200W / m 2 The product was irradiated with ultraviolet light for 1.4-1.8 hours, and the discharged product was washed with water and dried to obtain a composite flame retardant.

[0007] Furthermore, the feed ratio of pentaerythritol, phosphorus oxychloride, anhydrous zinc chloride and anhydrous dioxane is 0.1 mol: 0.1 mol: 0.1-0.12 g: 70-100 mL, and pentaerythritol and phosphorus oxychloride are subjected to an esterification reaction to form a phosphate compound containing a ring structure.

[0008] Furthermore, the feed ratio of methylvinyldichlorosilane, flame retardant matrix, triethylamine and acetonitrile is 0.1 mol: 55-60 mmol: 8-12 mL: 110-130 mL, and methylvinyldichlorosilane is used as a bridging material to react with the residual hydroxyl groups of the flame retardant matrix to form a compound containing double bonds and bibranched cyclic phosphates.

[0009] Furthermore, the feeding ratio of mica powder, silane coupling agent KH-580 and ethanol solution is 50g:5.5-7.5mL:85-100mL, the silane coupling agent KH-580 is hydrolyzed and coupled with the mica powder, and active thiol groups are grafted onto the particle surface of the mica powder for modification; Preferably, the average particle size of the mica powder is not higher than 30 μm, it can be evenly suspended and coupled in an ethanol solution, and is easily dispersed in a PVC matrix.

[0010] Furthermore, the feed ratio of the coupling matrix, the modified flame retardant, the photoinitiator 1173 and dimethylacetamide is 50g:9-11.5g:30-40mg:55-65mL. Under ultraviolet initiation, the modified flame retardant clicks with the thiol on the surface of the coupling matrix to be loaded onto its surface for compounding.

[0011] Furthermore, the plasticizer is one or more of dioctyl phthalate, diisooctyl phosphate and triethyl citrate.

[0012] Furthermore, the stabilizer is a composite of zinc stearate and calcium stearate.

[0013] Furthermore, the antioxidant is composed of antioxidant 1010 and antioxidant 168.

[0014] Furthermore, the lubricant is compounded by glyceryl stearate and polyethylene wax.

[0015] Beneficial effects of the present invention: The invention discloses a composite flame retardant, which can effectively improve the flame retardancy of a composite material by blending with a PVC material. The composite flame retardant uses mica powder as a core material, adopts a silane coupling agent KH-580 for surface treatment, introduces a large number of active mercapto groups into the surface for modification, forms a phosphate compound containing a ring structure by esterification of pentaerythritol and trichlorophosphorus oxychloride, namely a flame retardant matrix, and then uses methylvinyl dichlorosilane as a bridging material to perform a substitution reaction with the residual hydroxyl group of the flame retardant matrix to form a compound containing double bonds and double-branched cyclic phosphate ester, namely a modified flame retardant, and finally loads the modified flame retardant to the surface of the coupling matrix through a click reaction initiated by ultraviolet light with the mercapto group on the surface of the matrix for compounding; the phosphate organic structure on the surface of the composite flame retardant modifies the core mica powder, which is conducive to uniform dispersion during the melt blending process, and the dispersed mica powder forms a shielding layer, which can effectively improve the breakdown resistance of the composite material, and the mica powder It has high hardness and can improve the wear resistance of the PVC matrix to a certain extent, making it suitable for the service conditions of charging pile drag chains. In terms of flame retardancy, it is different from the existing organic and inorganic composite flame retardant systems. In the external combustion ignition environment, the organic phosphorus structure on the surface of the composite flame retardant is preferentially decomposed, and the generated phosphide promotes the PVC matrix near the surface of the core mica powder to preferentially carbonize and adhere to the surface of the core material, forming a mica powder-carbide layer, which hinders the deepening of combustion, and the carbonized layer on the surface of the core material plays a good transitional role between the un-ablated PVC matrix and the mica core material, avoiding the shedding of mica powder, maintaining the structural stability of the ablation layer, and still maintaining good protective effect after ablation. In the test, the UL94 flame retardant grade of the composite material reached V-0 level, and the sand falling abrasion rate of the ablation layer was 11.69-15.53%, which is much lower than the existing mica composite flame retardant system. DETAILED DESCRIPTION

[0016] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] Example 1, preparation of a highly flame-retardant PVC composite material for a charging pile drag chain, specifically as follows: (1) Preparation of composite flame retardant Step A1: Pentaerythritol, anhydrous zinc chloride and anhydrous dioxane are mixed and fed, dry nitrogen is introduced to replace the air in the reaction system, stirring is applied at 150 rpm, phosphorus oxychloride is slowly added, and the temperature is raised to 100° C. after addition, and refluxed. At the same time, an alkali drying tube filled with calcium oxide is used to absorb the reflux steam, and the reflux reaction is carried out for 6 hours, wherein the feed ratio of pentaerythritol, phosphorus oxychloride, anhydrous zinc chloride and anhydrous dioxane is 0.1 mol: 0.1 mol: 0.12 g: 100 mL. After the reaction is completed, dioxane is evaporated under reduced pressure to obtain a flame retardant matrix.

[0018] Step A2: Take a flame retardant substrate, triethylamine and acetonitrile and mix them, introduce dry nitrogen to replace the air in the reaction system, heat to 80°C, stir at 90rpm, slowly add methylvinyldichlorosilane and react for 12h, wherein the feed ratio of methylvinyldichlorosilane, flame retardant substrate, triethylamine and acetonitrile is 0.1mol:60mmol:12mL:130mL. After the reaction, acetonitrile is removed by rotary evaporation, the substrate is washed with water and vacuum dried to obtain a modified flame retardant.

[0019] Step A3: Mix the silane coupling agent KH-580 and a 45% volume fraction ethanol solution, adjust the pH value to 3 with formic acid and stir to hydrolyze for 1 hour, then add mica powder and stir to disperse, and let it stand for coupling for 24 hours, wherein the mica powder is selected from the GM-201 raw material of Anhui Ge Rui New Material Technology Co., Ltd., with an average particle size of 28μm, and the feed ratio of mica powder, silane coupling agent KH-580 and ethanol solution is 50g:7.5mL:100mL. After the reaction is completed, the bottom precipitate is taken and dried to obtain a coupling matrix.

[0020] Step A4: Take the modified flame retardant, photoinitiator 1173 and dimethylacetamide and mix them evenly, add the coupling matrix and mix them, add them into the grinder and grind them for 30 minutes to make pulp, heat the pulp to 90℃ and apply 200W / m 2 The mixture was irradiated with ultraviolet light for 1.4 h, wherein the feed ratio of the coupling matrix, the modified flame retardant, the photoinitiator 1173 and dimethylacetamide was 50 g:11.5 g:40 mg:65 mL. The material was washed with water, allowed to stand and the precipitate was dried to obtain a composite flame retardant.

[0021] (2) Preparation of composite materials The following raw materials are taken according to weight percentage: ABS resin 10wt%, selected from Toyolac™912 X01 U-type resin raw material; composite flame retardant 22wt%, self-made in this embodiment; plasticizer 12wt%, selected from industrial grade dioctyl phthalate and triethyl citrate in a mass ratio of 2:1; stabilizer 2.4wt%, selected from industrial grade zinc stearate and calcium stearate in a mass ratio of 1:1; antioxidant 0.3wt%, selected from industrial grade antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; lubricant 2.6wt%, selected from industrial grade stearic acid glyceryl ester and K0020F type polyethylene wax in a mass ratio of 2:1; PVC resin is supplemented to 100wt%, selected from SG-3 type resin raw material.

[0022] The above raw materials were mixed at 300 rpm for 10 min, transferred into a twin-screw extruder, the temperature in the melting zone was controlled at 200° C., and extruded into granules to obtain a highly flame-retardant PVC composite material for a charging pile drag chain.

[0023] Example 2, preparing a highly flame-retardant PVC composite material for a charging pile drag chain, specifically as follows: (1) Preparation of composite flame retardant Step A1: Pentaerythritol, anhydrous zinc chloride and anhydrous dioxane are mixed and fed, dry nitrogen is introduced to replace the air in the reaction system, stirring is applied at 120 rpm, phosphorus oxychloride is slowly added, and the temperature is raised to 100° C. after addition, and refluxed. At the same time, an alkali drying tube filled with calcium oxide is used to absorb the reflux steam, and the reflux reaction is carried out for 8 hours, wherein the feed ratio of pentaerythritol, phosphorus oxychloride, anhydrous zinc chloride and anhydrous dioxane is 0.1 mol: 0.1 mol: 0.1 g: 70 mL. After the reaction is completed, dioxane is evaporated under reduced pressure to obtain a flame retardant matrix.

[0024] Step A2: Take a flame retardant substrate, triethylamine and acetonitrile and mix them, introduce dry nitrogen to replace the air in the reaction system, heat to 75°C, stir at 60rpm, slowly add methylvinyldichlorosilane and react for 15h, wherein the feed ratio of methylvinyldichlorosilane, flame retardant substrate, triethylamine and acetonitrile is 0.1mol:55mmol:8mL:110mL. After the reaction, remove acetonitrile by rotary evaporation, wash the substrate with water and vacuum dry to obtain a modified flame retardant.

[0025] Step A3: Mix the silane coupling agent KH-580 and a 40% volume fraction ethanol solution, adjust the pH value to 4 with formic acid and stir to hydrolyze for 1.3 hours, then add mica powder and stir to disperse, and let it stand for coupling for 24 hours, wherein the mica powder is selected from the GM-2 type raw material of Anhui Ge Rui New Material Technology Co., Ltd., with an average particle size of 24μm, and the feed ratio of mica powder, silane coupling agent KH-580 and ethanol solution is 50g:5.5mL:85mL. After the reaction is completed, the bottom precipitate is taken and dried to obtain a coupling matrix.

[0026] Step A4: Take the modified flame retardant, photoinitiator 1173 and dimethylacetamide and mix them evenly, add the coupling matrix and mix them, add them into the grinder and grind them for 30 minutes to make pulp, heat the pulp to 70℃ and apply 150W / m 2 The mixture was irradiated with ultraviolet light for 1.8 h, wherein the feed ratio of the coupling matrix, the modified flame retardant, the photoinitiator 1173 and dimethylacetamide was 50 g:9 g:30 mg:55 mL. The material was washed with water, allowed to stand and the precipitate was dried to obtain a composite flame retardant.

[0027] (2) Preparation of composite materials The following raw materials are taken according to weight percentage: ABS resin 15wt%, selected from Toyolac™912 X01 U-type resin raw material; composite flame retardant 15wt%, self-made in this embodiment; plasticizer 16wt%, selected from industrial grade dioctyl phthalate and triethyl citrate in a mass ratio of 2:1; stabilizer 1.9wt%, selected from industrial grade zinc stearate and calcium stearate in a mass ratio of 1:1; antioxidant 0.25wt%, selected from industrial grade antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; lubricant 2.2wt%, selected from industrial grade stearic acid glyceryl ester and K0020F type polyethylene wax in a mass ratio of 2:1; PVC resin is supplemented to 100wt%, selected from SG-3 type resin raw material.

[0028] The above raw materials were mixed at 300 rpm for 10 min, transferred into a twin-screw extruder, the temperature in the melting zone was controlled at 200° C., and extruded into granules to obtain a highly flame-retardant PVC composite material for a charging pile drag chain.

[0029] Example 3, preparation of a highly flame-retardant PVC composite material for a charging pile drag chain, specifically as follows: (1) Preparation of composite flame retardant Step A1: Take pentaerythritol, anhydrous zinc chloride and anhydrous dioxane and mix them into a mixture, introduce dry nitrogen to replace the air in the reaction system, apply stirring at 150 rpm, slowly add phosphorus oxychloride, raise the temperature to 100°C and reflux after adding, and use an alkali drying tube filled with calcium oxide to absorb the reflux steam, and reflux for 7 hours, wherein the feed ratio of pentaerythritol, phosphorus oxychloride, anhydrous zinc chloride and anhydrous dioxane is 0.1 mol: 0.1 mol: 0.1 g: 90 mL. After the reaction is completed, dioxane is evaporated under reduced pressure to obtain a flame retardant matrix.

[0030] Step A2: Take a flame retardant substrate, triethylamine and acetonitrile and mix them, introduce dry nitrogen to replace the air in the reaction system, heat to 80°C, stir at 90rpm, slowly add methylvinyldichlorosilane and react for 14h, wherein the feed ratio of methylvinyldichlorosilane, flame retardant substrate, triethylamine and acetonitrile is 0.1mol:55mmol:10mL:120mL. After the reaction, acetonitrile is removed by rotary evaporation, the substrate is washed with water and vacuum dried to obtain a modified flame retardant.

[0031] Step A3: Mix the silane coupling agent KH-580 and a 40% volume fraction ethanol solution, adjust the pH value to 3 with formic acid and stir to hydrolyze for 1.2 hours, then add mica powder and stir to disperse, and let it stand for coupling for 24 hours, wherein the mica powder is selected from the GM-3 raw material of Anhui Ge Rui New Material Technology Co., Ltd., with an average particle size of 18μm, and the feed ratio of mica powder, silane coupling agent KH-580 and ethanol solution is 50g:6mL:90mL. After the reaction is completed, the bottom precipitate is taken and dried to obtain a coupling matrix.

[0032] Step A4: Take the modified flame retardant, photoinitiator 1173 and dimethylacetamide and mix them evenly, add the coupling matrix and mix them, add them into the grinder and grind them for 30 minutes to make pulp, heat the pulp to 85℃ and apply 150W / m 2 The mixture was irradiated with ultraviolet light for 1.5 h, wherein the feed ratio of the coupling matrix, the modified flame retardant, the photoinitiator 1173 and dimethylacetamide was 50 g:10 g:30 mg:60 mL. The material was washed with water, allowed to stand and the precipitate was dried to obtain a composite flame retardant.

[0033] (2) Preparation of composite materials The following raw materials are taken according to weight percentage: ABS resin 12wt%, selected from Toyolac™912 X01 U-type resin raw material; composite flame retardant 18wt%, self-made in this embodiment; plasticizer 15wt%, selected from industrial grade dioctyl phthalate and triethyl citrate in a mass ratio of 2:1; stabilizer 12.2wt%, selected from industrial grade zinc stearate and calcium stearate in a mass ratio of 1:1; antioxidant 0.25wt%, selected from industrial grade antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; lubricant 2.4wt%, selected from industrial grade stearic acid glyceryl ester and K0020F type polyethylene wax in a mass ratio of 2:1; PVC resin is supplemented to 100wt%, selected from SG-3 type resin raw material.

[0034] The above raw materials were mixed at 300 rpm for 10 min, transferred into a twin-screw extruder, the temperature in the melting zone was controlled at 200° C., and extruded into granules to obtain a highly flame-retardant PVC composite material for a charging pile drag chain.

[0035] Comparative Example This comparative example refers to Example 3, except that the composite flame retardant is replaced by 16 wt % of the coupling matrix and 2 wt % of the flame retardant DOPO in Example 3, and the rest of the implementation process is exactly the same.

[0036] The composite materials prepared in the examples and comparative examples were placed in a flat vulcanizer and hot pressed into sheets with a thickness of 5 mm. Samples were taken for tensile testing according to GB / T 1040.1-2018 standard, and flame retardancy testing was performed using a UL94 combustion test machine. The specific test results are shown in Table 1: Table 1

[0037] It can be seen from the test results in Table 1 that the mechanical properties of the composite materials of the embodiment and the comparative example are similar, and the fracture toughness is slightly higher than that of the comparative example, and both can meet the use requirements of the charging pile drag chain. The flame retardant grade of the embodiment reaches V-0 level, showing high flame retardancy.

[0038] In order to simulate the state of the composite material after combustion, an alcohol burner was used to burn the sample vertically. The flame core was 10 mm away from the sample surface. The sample moving rate was 500 mm / min and the burning time was 5 min. After cooling for 2 h, the wear test was carried out by the falling sand abrasion method. The falling sand speed was 22 g / min. The calculation of the combustion weight loss rate = (initial mass - mass after combustion) / initial mass × 100%, the falling sand abrasion rate = (mass after combustion - mass after falling sand) / mass after combustion × 100%. The specific test results are shown in Table 2: Table 2

[0039] During the continuous combustion test as above, a lot of falling objects appeared. It can be seen from the test results in Table 2 that the combustion weight loss rate of the comparative example is higher than that of the embodiment. In the sand falling test after combustion, the sand falling abrasion rate of the embodiment is much lower than that of the comparative example. The stability of the combustion layer is high, which can play a good protective role.

[0040] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0041] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A highly flame-retardant PVC composite material for a charging pile drag chain, characterized in that: The invention is composed of the following components: 10-15wt% of ABS resin, 15-22wt% of composite flame retardant, 12-16wt% of plasticizer, 1.9-2.4wt% of stabilizer, 0.25-0.3wt% of antioxidant and 2.2-2.6wt% of lubricant, and the balance is PVC resin; The composite flame retardant is prepared by the following method: Step A1: pentaerythritol, anhydrous zinc chloride and anhydrous dioxane are mixed and added, dry nitrogen is introduced to replace the air in the reaction system, phosphorus oxychloride is slowly added while stirring, and after the addition, the temperature is raised to reflux and the reflux steam is absorbed by an alkali drying tube, and the reflux time is controlled to be 6-8 hours. After the reaction is completed, dioxane is removed to obtain a flame retardant matrix; Step A2: the flame retardant substrate, triethylamine and acetonitrile are mixed, dry nitrogen is introduced to replace the air in the reaction system, the temperature is raised to 75-80° C., methylvinyldichlorosilane is slowly added with stirring to react for 12-15 hours, acetonitrile is removed after the reaction is completed, the substrate is washed with water and vacuum dried to obtain a modified flame retardant; Step A3: Mix the silane coupling agent KH-580 and the ethanol solution, adjust the pH value to 3-4 with formic acid and stir to hydrolyze for 1-1.3 hours, then add the mica powder and stir to disperse, let it stand for coupling for 24 hours, take the bottom precipitate and dry it to obtain a coupling matrix; Step A4: Mix the modified flame retardant, photoinitiator 1173 and dimethylacetamide, add the coupling matrix, mix and grind to make slurry, heat the slurry to 70-90°C and apply 150-200W / m 2 The product was irradiated with ultraviolet light for 1.4-1.8 hours, and the discharged product was washed with water and dried to obtain a composite flame retardant.

2. A highly flame-retardant PVC composite material for a charging pile drag chain according to claim 1, characterized in that: The feed ratio of pentaerythritol, phosphorus oxychloride, anhydrous zinc chloride and anhydrous dioxane is 0.1 mol: 0.1 mol: 0.1-0.12 g: 70-100 mL.

3. A highly flame-retardant PVC composite material for a charging pile drag chain according to claim 2, characterized in that: The feed ratio of methylvinyldichlorosilane, flame retardant matrix, triethylamine and acetonitrile is 0.1 mol: 55-60 mmol: 8-12 mL: 110-130 mL.

4. A highly flame-retardant PVC composite material for a charging pile drag chain according to claim 1, characterized in that: The feeding ratio of mica powder, silane coupling agent KH-580 and ethanol solution is 50g:5.5-7.5mL:85-100mL.

5. A highly flame-retardant PVC composite material for a charging pile drag chain according to claim 4, characterized in that: The average particle size of the mica powder is not higher than 30 μm.

6. A highly flame-retardant PVC composite material for a charging pile drag chain according to any one of claims 3-4, characterized in that: The feed ratio of the coupling matrix, the modified flame retardant, the photoinitiator 1173 and dimethylacetamide is 50g:9-11.5g:30-40mg:55-65mL.

7. The highly flame-retardant PVC composite material for a charging pile drag chain according to claim 1, characterized in that: The plasticizer is one or more of dioctyl phthalate, diisooctyl phosphate and triethyl citrate.

8. The highly flame-retardant PVC composite material for a charging pile drag chain according to claim 1, characterized in that: The stabilizer is a compound of zinc stearate and calcium stearate.

9. The highly flame-retardant PVC composite material for a charging pile drag chain according to claim 1, characterized in that: The antioxidant is compounded by antioxidant 1010 and antioxidant 168.

10. The highly flame-retardant PVC composite material for a charging pile drag chain according to claim 1, characterized in that: The lubricant is a compound of glyceryl stearate and polyethylene wax.

Citation Information

Cited By

  • High-temperature-resistant PPS cable sheath and preparation method thereof

    CN120464199A

  • High temperature resistant PPS cable sheath and preparation method thereof

    CN120464199B